Development of Noise Reduction Panel Using Piezoelectric Material. (2016) - Babu, J.; Ramacahndran, Adarsh; Philip, Jose; Chandran, C. Sarath
Abstract: Workplace noise is hazardous to worker safety and health. Noise can not only cause hearing impairment but also act as a causal factor for stress and raise the systolic blood pressure.There are many methods available and being used in industries at present to reduce acoustic emissions from various equipment. The process of reducing sound emissions from equipment is called acoustic quieting. The method of using piezoelectric material to reduce transmitted sound from equipment rather than damping structural vibration can be applied where it is difficult to damp structural vibrations completely. If piezoelectric materials are attached to vibrating machine parts, withthe supply of suitable voltages, they counter-vibrate which helps in damping structural vibration. Previous studies conducted using simulations with the help of ANSYS software showed noise reductions of up to20 decibels. This paper presentsan effective technique for tuning the frequencies of vibrations of the piezoelectric material with the source vibrations for the reduction of noise. It can help in cancelling the original vibrations which ultimately lead to the reduction in transmitted noise levels. Experiments reveal that a reduction of 9 decibels innoise level is possible by using a filtercontrol circuit.